2020
DOI: 10.13031/trans.14020
|View full text |Cite
|
Sign up to set email alerts
|

Denitrifying Woodchip Bioreactor Leachate Tannic Acid and True Color: Lab and Field Studies

Abstract: HighlightsOak leached more tannic acid, true color, and chemical oxygen demand (COD) than ash and mixed hardwood chips.The factors became similar (tannic acid, COD) or below stream levels (true color) after flushing.Eleven site-years of field bioreactor data showed decreasing tannic acid and true color over time.Post-startup tannic acid was lower in bioreactor outflow than in area streams.True color did not appear to be a reliable indicator of leachate tannic acid at low concentrations.Abstract. Woodchips have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The bioreactors were packed with either EAB-killed ash woodchips, oak woodchips (Quercus rubra), or a "mixed hardwood" blend of commercially supplied woodchips. The previous study evaluated tannic acid leaching and leachate true color to assess that aspect of high-tannin oak wood in bioreactors (Wickramarathne et al, 2020). A major procedural difference between the previous study, where only nine bioreactors were evaluated, and the present study was that nine additional bioreactors containing an upstream rock filter were included here.…”
Section: Bioreactor Operation and Water Chemistrymentioning
confidence: 94%
See 2 more Smart Citations
“…The bioreactors were packed with either EAB-killed ash woodchips, oak woodchips (Quercus rubra), or a "mixed hardwood" blend of commercially supplied woodchips. The previous study evaluated tannic acid leaching and leachate true color to assess that aspect of high-tannin oak wood in bioreactors (Wickramarathne et al, 2020). A major procedural difference between the previous study, where only nine bioreactors were evaluated, and the present study was that nine additional bioreactors containing an upstream rock filter were included here.…”
Section: Bioreactor Operation and Water Chemistrymentioning
confidence: 94%
“…Eighteen rectangular Plexiglas R denitrifying bioreactors (15 × 15 × 20 cm) were constructed and operated as previously described by Wickramarathne et al (2020). The bioreactors were packed with either EAB-killed ash woodchips, oak woodchips (Quercus rubra), or a "mixed hardwood" blend of commercially supplied woodchips.…”
Section: Bioreactor Operation and Water Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Many small-scale bioreactor fill media comparisons have reported these start-up nutrient flushing issues (e.g., Gibert et al, 2008;Cameron and Schipper, 2010;Healy et al, 2012), and colored bioreactor outflow water has been observed during start-up at the field-scale (e.g., the Belgium section above). Additional woodchip leaching concerns, such as phenols and tannic acid, are starting to be investigated (Wickramarathne et al, 2020;Lepine et al, 2020b). These issues subside given sufficient flushing, which has ranged from 15 to roughly 300 cumulative pore volumes, or from a week to approximately six months, depending on the bioreactor size, fill media, and initial flow rate (Healy et al, 2012;von Ahnen et al, 2016;Wickramarathne et al, 2020).…”
Section: Limitations and Tradeoffsmentioning
confidence: 99%
“…Additional woodchip leaching concerns, such as phenols and tannic acid, are starting to be investigated (Wickramarathne et al, 2020;Lepine et al, 2020b). These issues subside given sufficient flushing, which has ranged from 15 to roughly 300 cumulative pore volumes, or from a week to approximately six months, depending on the bioreactor size, fill media, and initial flow rate (Healy et al, 2012;von Ahnen et al, 2016;Wickramarathne et al, 2020).…”
Section: Limitations and Tradeoffsmentioning
confidence: 99%